To solve the quadratic equation \( x^2 + 12x = -20 \) and answer the questions in parts A through D, we will go step by step.
Part A:
We want to find the value of \( c \) such that \( x^2 + 12x + c \) becomes a perfect square trinomial.
A perfect square trinomial can be expressed in the form \( (x + a)^2 = x^2 + 2ax + a^2 \). Here, \( 2a = 12 \), so:
\[ a = \frac{12}{2} = 6. \]
Therefore, \( c = a^2 = 6^2 = 36 \).
Thus, the value of \( c \) that makes the equation a perfect square trinomial is:
Part A: c = 36
Part B:
Next, we can rewrite the equation as:
\[ x^2 + 12x + 36 = -20 + 36. \]
This simplifies the right side:
\[ x^2 + 12x + 36 = 16. \]
Now, we can factor the left side:
\[ (x + 6)^2 = 16. \]
Thus, our equation in the form \( (x - h)^2 = k \) is:
Part B: (x + 6)² = 16
Part C:
To solve the equation \( (x + 6)^2 = 16 \), we take the square root of both sides:
\[ x + 6 = \pm 4. \]
This provides us with two equations:
- \( x + 6 = 4 \)
- \( x + 6 = -4 \)
For \( x + 6 = 4 \):
\[ x = 4 - 6 = -2. \]
For \( x + 6 = -4 \):
\[ x = -4 - 6 = -10. \]
The lesser number is:
Part C: x = -10
Part D:
The greater number is:
Part D: x = -2
Final answers:
- Part A: c = 36
- Part B: (x + 6)² = 16
- Part C: x = -10
- Part D: x = -2